New Florida Foliage Plant Cultivar: 'Emerald Bay' Aglaonema - Richard J. Henny; Jianjun Chen; Terri A. Mellich (EDIS)
ENH-1091, a 3-page illustrated fact sheet by R.J. Henny, J. Chen, and T.A. Mellich, describes a new cultivar of this important foliage plant which shares many traits of the popular 'Golden Bay', but without the yellow background coloration in the leaves and petioles — its origin, description, performance, and availability. Includes references. Published by the UF Department of Environmental Horticulture, February 2009.